PHYTOCHEMICAL ANALYSIS AND EVALUATION OF ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES OF VITEX NEGUNDO AND OPHIORRHIZA MUNGOS - A. JAYADEV; S. SARI (The Bioscan, 2013)
Phytochemical analysis of the crude extracts revealed the presence of various primary and secondary metabolites. Nine bacteria including both gram positive and gram negative, (B. subtilis, L. lactis, S. aureus, M. luteus, P. aeruginosa S. typhimurium, K. pneumoniae, P. vulgaris, and E. coli) were tested for susceptibility to the extracts using disc diffusion method. The results were compared with antibiotic ampicillin which was used as the standard. Potent antimicrobial activity was shown by ethyl acetate extract and methanol extract of leaf and stem of O. mungose (sensitivity zone - 19 – 28mm for Ethyl acetate and 11 – 26mm respectively) and ethanol extract of leaf and stem of V. negundo (sensitivity zone - 9 – 16mm). The methanol extracts of leaf and stem of O. mungos and V. negundo, were analyzed using methods such as analysis of total phenolic content, reducing power and DPPH free radical scavenging assay for antioxidant activity determination. The highest free radical scavenging was shown by V. negundo stem (96.47% at 100 μg/mL), nearest to that of the ascorbic acid (97.44% at 100μg/ mL) which was used as the standard. The activity shown by O.mungos stem was considerably lower with the least activity of 4.06% in the concentration 20 μg/mL.